Early angiotensin-converting enzyme inhibition in Alport syndrome delays renal failure and improves life expectancy - Gross, Oliver; Tönshoff, Burkhard; Höcker, Britta (Kidney international, 2012)
Alport syndrome inevitably leads to end-stage renal disease and there are no therapies known to improve outcome. Here we determined whether angiotensin-converting enzyme inhibitors can delay time to dialysis and improve life expectancy in three generations of Alport families. Patients were categorized by renal function at the initiation of therapy and included 33 with hematuria or microalbuminuria, 115 with proteinuria, 26 with impaired renal function, and 109 untreated relatives. Patients were followed for a period whose mean duration exceeded two decades. Untreated relatives started dialysis at a median age of 22 years. Treatment of those with impaired renal function significantly delayed dialysis to a median age of 25, while treatment of those with proteinuria delayed dialysis to a median age of 40. Significantly, no patient with hematuria or microalbuminuria advanced to renal failure so far. Sibling pairs confirmed these results, showing that earlier therapy in younger patients significantly delayed dialysis by 13 years compared to later or no therapy in older siblings. Therapy significantly improved life expectancy beyond the median age of 55 years of the no-treatment cohort. Thus, Alport syndrome is treatable with angiotensin-converting enzyme inhibition to delay renal failure and therapy improves life expectancy in a time-dependent manner. This supports the need for early diagnosis and early nephroprotective therapy in oligosymptomatic patients.